Copper alloy wire and method for producing the same

JP7608049B2Active Publication Date: 2025-01-06FURUKAWA ELECTRIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019529676
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-20
Filing Date
2019-02-18
Publication Date
2025-01-06
Estimated Expiration
2039-02-18

AI Technical Summary

Benefits of technology

【0009】 本発明の態様によれば、1.5~6.0質量%のAg、0~1.0質量%のMg、0~1.0質量%のCr及び0~1.0質量%のZrを含有し、残部がCu及び不可避不純物からなる合金組成を有する銅合金線材について、長手方向に対し平行な断面における240nm×360nmの観察域でのCuに整合して析出している析出物の面積割合(A)が、上記範囲内であることにより、優れた導電率を損なうことなく、線材を細径化した場合でも、引張強度に優れた銅合金線材を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608049000002
    Figure 0007608049000002
  • Figure 0007608049000003
    Figure 0007608049000003
  • Figure 0007608049000004
    Figure 0007608049000004
Patent Text Reader

Abstract

An object of the present invention is to provide a copper alloy wire rod that has excellent tensile strength even when the diameter of the wire rod is reduced without impairing the excellent electrical conductivity, and a method for producing the same. A copper alloy wire having an alloy composition containing 1.5 to 6.0 mass% of Ag, 0 to 1.0 mass% of Mg, 0 to 1.0 mass% of Cr, and 0 to 1.0 mass% of Zr, with the balance being Cu and unavoidable impurities, wherein when a cross section parallel to a longitudinal direction of the copper alloy wire is observed, an area ratio (A) of precipitates that are coherently precipitated with Cu in a parent phase in a rectangular observation area of ​​240 nm × 360 nm satisfies the following formula (I): (0.393×x-0.589)%≦A≦(3.88×x-5.81)% (I) (wherein x represents the mass % of Ag)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper alloy wire having high tensile strength that can be used for, for example, tinsel wire, and a method for manufacturing the copper alloy wire. [Background technology]

[0002] For example, a speaker is equipped with a coil and a diaphragm, and when a current flows through the coil, the coil vibrates, and the diaphragm vibrates in conjunction with the vibration of the coil to produce sound. A tinsel wire is used for the wire that connects the coil and the substrate terminal. Therefore, the tinsel wire is required to have high vibration durability to withstand vibrations caused by sound. Due to the dimensional effect, vibration durability is generally improved by processing the wire into a thinner shape. On the other hand, when the wire is made thinner, the tensile durability decreases, making it difficult to handle during wire manufacturing, and there is a problem that breakage, tangling, etc. occur, resulting in poor yield.

[0003] Therefore, for example, as an alloy material with improved tensile strength, a copper alloy has been proposed that contains 8.0 to 20.0 wt. % Ag, 0.1 to 1.0 wt. % Cr, with the remainder being Cu and unavoidable impurities, and has a structure in which fine Cr precipitates are dispersed in a matrix in which primary crystals and eutectic crystals are oriented in a fibrous form (Patent Document 1).

[0004] However, in Patent Document 1, fine Cr precipitates are merely dispersed in a matrix in which primary crystals and eutectic crystals are oriented in a fibrous form, and the precipitation state of the fine Cr precipitates is not controlled in the structure.

[0005] Therefore, in the copper alloy of Patent Document 1, when the diameter of the wire is reduced, there is room for improvement in tensile strength, and further, there is room for improvement in improving the handleability during wire production and in preventing breakage, tangling, and the like, thereby improving yield. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Application No. 5-90832 Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above circumstances, an object of the present invention is to provide a copper alloy wire having excellent tensile strength even when the wire is made thin without impairing excellent electrical conductivity, and a method for producing the same. [Means for solving the problem]

[0008] [1] A copper alloy wire having an alloy composition containing 1.5 to 6.0 mass% Ag, 0 to 1.0 mass% Mg, 0 to 1.0 mass% Cr, and 0 to 1.0 mass% Zr, with the balance being Cu and unavoidable impurities; When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the area ratio (A) of precipitates precipitated in a rectangular observation area of ​​240 nm × 360 nm that is consistent with Cu of the parent phase is The following formula (I) (0.393×x-0.589)%≦A≦(3.88×x-5.81)% (I) (In formula (I), x represents mass % of Ag.) Copper alloy wire within the range. [2] The copper alloy wire according to [1], wherein the total content of at least one component selected from the group consisting of Mg, Cr and Zr is 0.01 to 3.0 mass %. [3] The copper alloy wire according to [1] or [2], wherein the precipitates, which are precipitated in conformity with the Cu of the parent phase, are present in a fibrous form along the longitudinal direction of the copper alloy wire. [4] When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the average width (W) of the precipitates that are precipitated in conformity with the Cu of the parent phase in a rectangular observation area of ​​240 nm × 360 nm is The following formula (II) (8.3×d)nm≦W≦(24.9×d)nm (II) (In formula (II), d represents the wire diameter (mm) of the copper alloy wire.) The copper alloy wire according to [3], [5] When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the average length (L) of the precipitates precipitated in conformity with the Cu of the parent phase in a rectangular observation area of ​​240 nm × 360 nm is The following formula (III) (11.3 / d)nm≦L≦(33.8 / d)nm (III) (In formula (III), d represents the wire diameter (mm) of the copper alloy wire.) The copper alloy wire according to [3] or [4], wherein the copper alloy wire is within the range of [6] When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the average interval (S) of the precipitates that are precipitated in a coordinated manner with the Cu of the parent phase in a rectangular observation area of ​​240 nm × 360 nm is The following formula (IV) (760×x^-2.25)×dnm≦S≦(2300×x^-2.25)×dnm (IV) (In formula (IV), d represents the wire diameter (mm) of the copper alloy wire, and x represents the mass% of Ag.) The copper alloy wire according to any one of [3] to [5], wherein the copper alloy wire is within the range of [7] The copper alloy wire according to any one of [1] to [6], wherein the precipitates are aligned in the same crystal axis direction with respect to the Cu of the parent phase. [8] A method for producing a copper alloy wire according to any one of [1] to [7], comprising the steps of: melting a raw material; casting the melted raw material to obtain an ingot; subjecting the copper alloy material obtained from the ingot to a first heat treatment; further subjecting the copper alloy material obtained from the second heat treatment to a final wire drawing process to obtain a copper alloy wire, The first heat treatment step is carried out at a temperature of 700° C. or higher, The second heat treatment step is carried out at a temperature of 350 to 600°C, The degree of processing loge(A0 / A1 )(In the formula, A0 is the cross-sectional area in the direction perpendicular to the longitudinal direction of the copper alloy material immediately before the final wire drawing, and A1 is the cross-sectional area in the direction perpendicular to the longitudinal direction of the copper alloy material immediately after the final wire drawing) is 2.5 or more. [9] The method for producing a copper alloy wire according to [8], wherein a wire drawing process is performed between the step of obtaining the ingot and the first heat treatment step, and / or between the first heat treatment step and the second heat treatment step. Effect of the Invention

[0009] According to an embodiment of the present invention, for a copper alloy wire having an alloy composition containing 1.5 to 6.0 mass% Ag, 0 to 1.0 mass% Mg, 0 to 1.0 mass% Cr, and 0 to 1.0 mass% Zr, with the remainder being Cu and unavoidable impurities, the area ratio (A) of precipitates precipitated in conformity with Cu in an observation area of ​​240 nm x 360 nm in a cross section parallel to the longitudinal direction is within the above range, so that a copper alloy wire having excellent tensile strength can be obtained without impairing excellent electrical conductivity, even when the wire is made thin.

[0010] In this way, even when the diameter of the wire is reduced, a copper alloy wire having excellent tensile strength can be obtained, so that high vibration durability is obtained while improving the handleability during wire production. In addition, breakage and tangling of the wire are prevented, thereby improving the yield.

[0011] According to an embodiment of the present invention, the total content of at least one component selected from the group consisting of Mg, Cr, and Zr is 0.01 to 3.0 mass%, which contributes to further improving the vibration durability and further improving the tensile strength even when the wire rod is made thinner.

[0012] According to an embodiment of the present invention, the precipitates that are precipitated in conformity with the Cu of the parent phase are present in a fibrous form along the longitudinal direction of the copper alloy wire, and the average width (W) of the fibrous precipitates, the average length (L) of the precipitates and / or the average spacing (S) of the precipitates are within the above-mentioned ranges, which contributes to further improvement of the vibration durability and further improvement of the tensile strength even when the wire is made thinner. [Brief description of the drawings]

[0013] [Figure 1] This is an electron microscope photograph of a diffraction spot that occurs when an electron beam is incident on a Cu crystal in the <0010> direction. [Diagram 2] 1 is an electron microscope photograph showing a dark field image of a copper alloy wire. [Diagram 3] 13 is a graph showing the results of calculating the number of pixels in a white contrast portion for each row in a dark-field image whose contrast has been binarized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The copper alloy wire of the present invention is described in detail below. The copper alloy wire of the present invention is a copper alloy wire having an alloy composition containing 1.5 to 6.0 mass% Ag, 0 to 1.0 mass% Mg, 0 to 1.0 mass% Cr, and 0 to 1.0 mass% Zr, with the balance being Cu and unavoidable impurities. When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the area ratio (A) of precipitates that are precipitated in a coordinated manner with Cu in the parent phase in a rectangular observation area of ​​240 nm × 360 nm satisfies the following formula (I): (0.393×x-0.589)%≦A≦(3.88×x-5.81)% (I) (In formula (I), x represents the mass % of Ag.)

[0015] [Alloy composition of copper alloy wire] The copper alloy wire of the present invention contains 1.5 to 6.0 mass% of Ag (silver). Therefore, Ag is an essential additive component. Ag exists in a state of being dissolved in the parent phase Cu (copper), or in a state of being crystallized and precipitated as second-phase particles during casting of the copper alloy material, or in a state of being precipitated as second-phase particles by heat treatment after casting of the copper alloy material (hereinafter, these are collectively referred to as "precipitates" in this specification), and is an element that exerts the effect of solid solution strengthening or dispersion strengthening. The second phase means a crystal having a different crystal structure from the parent phase (first phase) of Cu.

[0016] If the Ag content is less than 1.5 mass%, the effect of solid solution strengthening or dispersion strengthening is insufficient, and sufficient tensile strength and vibration durability cannot be obtained. On the other hand, if the Ag content exceeds 6.0 mass%, sufficient electrical conductivity cannot be obtained, and the raw material cost also increases. From the above, in order to obtain excellent tensile strength even when the wire is thinned without impairing electrical conductivity, the Ag content is set to 1.5 to 6.0 mass%. Although the requirements for tensile strength and electrical conductivity differ depending on the application of the copper alloy wire, it is possible to set the balance between tensile strength and electrical conductivity as desired by adjusting the Ag content within the range of 1.5 to 6.0 mass%. Since a balance between tensile strength and electrical conductivity can be obtained in a wide range of applications, the Ag content is preferably 1.5 to 4.5 mass%.

[0017] In the copper alloy wire of the present invention, in addition to Ag, which is an essential additive component, at least one element selected from the group consisting of Mg (magnesium), Cr (chromium), and Zr (zirconium) may be further contained as an optional additive component.

[0018] Mg, Cr, and Zr are all elements that exist mainly in the form of solid solution or second phase in the Cu matrix, and exhibit the effect of solid solution strengthening or dispersion strengthening, similar to the case of Ag. Furthermore, when contained together with Ag, they exist as a second phase of a ternary or higher system, such as a Cu-Ag-Zr system, and can contribute to further solid solution strengthening or dispersion strengthening.

[0019] From the above, in order to fully exert the effect of solid solution strengthening or dispersion strengthening, the total content of at least one component selected from the group consisting of Mg, Cr and Zr is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and particularly preferably 0.10 mass% or more. On the other hand, if the contents of Mg, Cr and Zr each exceed 1.0 mass%, excellent electrical conductivity may not be obtained depending on the application, so the contents of Mg, Cr and Zr are preferably 1.0 mass% or less, more preferably 0.7 mass% or less, and particularly preferably 0.5 mass% or less. Therefore, in order to obtain excellent tensile strength even when the wire is thinned without impairing electrical conductivity, the total content of at least one component selected from the group consisting of Mg, Cr and Zr is preferably 0.01 to 3.0 mass%, more preferably 0.05 to 2.1 mass%, and particularly preferably 0.10 to 1.5 mass%.

[0020] The remainder other than the above-mentioned components is Cu and inevitable impurities. Cu is the parent phase of the copper alloy wire of the present invention. In the parent phase Cu, Ag, which is an essential additive component, exists in a solid solution state or in a precipitated state. In addition, if necessary, at least one component selected from the group consisting of Mg, Cr, and Zr, which is an optional additive component, exists in the parent phase Cu in a solid solution state or in a precipitated state.

[0021] The inevitable impurities refer to impurities at a content level that may be inevitably contained in the manufacturing process of the copper alloy wire of the present invention. The inevitable impurities may be a factor that reduces the electrical conductivity depending on the content. Therefore, in consideration of the decrease in electrical conductivity, it is preferable to suppress the content of the inevitable impurities. Examples of the inevitable impurities include Ni, Sn, and Zn.

[0022] [Area ratio of precipitates that are coherently precipitated with Cu in the parent phase (A)] In the copper alloy wire of the present invention, when a cross section parallel to the longitudinal direction is observed, the area ratio (A) of precipitates that are precipitated coherently with Cu of the parent phase in a rectangular observation area of ​​240 nm × 360 nm (hereinafter, sometimes referred to as "coherent precipitates") is expressed by the following formula (I): (0.393×x-0.589)%≦A≦(3.88×x-5.81)% (I) (In formula (I), x represents the mass % of Ag.)

[0023] Therefore, in the copper alloy wire of the present invention, the range of the area ratio (A) of the coherent precipitates also changes according to the change in the Ag content. By keeping the area ratio (A) of the coherent precipitates within the above range, it is possible to obtain a copper alloy wire having excellent tensile strength and vibration durability even when the wire is thinned without impairing the excellent electrical conductivity. The above formula (I) was derived from the results of experiments in which the Ag content in the copper alloy wire was selected in various ways.

[0024] When the area ratio (A) of the coherent precipitates is less than (0.393×x-0.589)%, the amount of the coherent precipitates is small, so the coherent precipitates do not hinder the deformation of the copper alloy wire, and as a result, excellent tensile strength and vibration durability are not obtained. On the other hand, when the area ratio (A) of the coherent precipitates is more than (3.88×x-5.81)%, the dimensions of the coherent precipitates, such as length and width, become large, so that the coherent precipitates do not hinder the deformation of the copper alloy wire, and as a result, excellent tensile strength and vibration durability are not obtained.

[0025] Since the coherent precipitates are mainly composed of Ag, the area ratio (A) of the coherent precipitates varies depending on the Ag content. That is, it is considered that the area ratio (A) increases as the Ag content increases, and the area ratio (A) decreases as the Ag content decreases. If the area ratio (A) of the coherent precipitates increases, the coherent precipitates hinder the deformation of the copper alloy wire, and as a result, the tensile strength and vibration durability are improved. On the other hand, it was found that even if the area ratio (A) of the coherent precipitates is excessive, the coherent precipitates do not hinder the deformation of the copper alloy wire, and as a result, excellent tensile strength and vibration durability cannot be obtained. Therefore, in the copper alloy wire of the present invention, by adjusting not only the range of the Ag content but also the range of the area ratio (A) of the coherent precipitates, excellent tensile strength and vibration durability are realized without impairing the electrical conductivity.

[0026] [Precipitates coherently with Cu in the matrix] In this specification, the above-mentioned "precipitated coherently with Cu of the parent phase" means that the precipitate has a certain crystal orientation with respect to the crystal of Cu of the parent phase. As a method for determining whether or not the precipitate has a certain crystal orientation with respect to the crystal of Cu of the parent phase, that is, whether or not the precipitate is a coherent precipitate, there is a method of reading from the diffraction pattern.

[0027] When an electron beam is irradiated onto a sample in a transmission electron microscope, the electron beam diffracts. The diffracted waves generated by the diffraction of the electron beam are strengthened or weakened depending on the type of crystal and the atomic spacing that makes up the crystal, creating a specific diffraction pattern depending on the crystal. For example, when an electron beam is incident on a Cu crystal in the

[0010] direction, diffraction spots are generated at the vertices and midpoint of a square, as shown in Figure 1.

[0028] Cu and Ag have the same face-centered cubic lattice structure (fcc structure), so their diffraction patterns are the same, but the spacing between diffraction spots is different because their lattice constants are different. The larger the lattice constant, the narrower the spacing between diffraction spots, so the Ag diffraction spots appear in a narrower range than the Cu diffraction spots. If Ag precipitates exist in a Cu alloy and the crystals of the Ag precipitates are aligned in a specific direction, the diffraction spots of the Ag precipitates will appear slightly inside the diffraction spots of the parent phase Cu. If the crystal orientation of Cu and the crystal orientation of Ag are completely consistent, that is, if both the Cu crystals and the Ag crystals are oriented in the

[0100] direction, the diffraction patterns are the same, and the Ag diffraction pattern appears slightly inside the Cu diffraction pattern.

[0029] On the other hand, if Cu and Ag are aligned in a specific direction but the crystal orientation of Cu and Ag do not completely match, for example, if the Cu crystals are oriented in the

[0100] direction while the Ag crystals are oriented in the

[0110] direction relative to the observation axis

[0100] direction, a diffraction pattern corresponding to the

[0100] direction of Cu and a diffraction pattern corresponding to the

[0110] direction of Ag will appear.

[0030] From the above, when the diffraction pattern of Cu and the diffraction pattern of Ag are identical and the diffraction pattern of Ag appears slightly inside the diffraction pattern of Cu, or when a diffraction pattern of Cu indicating that the Cu crystals correspond to a specified direction and a diffraction pattern of Ag indicating that the Ag crystals correspond to a specified direction appear, it is determined that Ag is "precipitated in conformity with the Cu parent phase", i.e., the Ag precipitates are conformal with the Cu parent phase.

[0031] However, when Cu and Ag are not aligned at all, that is, when the crystal orientation of Cu and Ag do not match at all, Ag is arranged in various crystal directions relative to Cu, and the diffraction pattern of Ag is formed randomly relative to the diffraction pattern of Cu. In this case, it is determined that the Ag precipitates are not aligned with the Cu parent phase.

[0032] [Average width (W) of precipitates that are coherent with the Cu in the matrix] It is more effective if the precipitates coherently precipitated with the Cu of the parent phase are present in a fibrous form along the longitudinal direction of the copper alloy wire, i.e., if they are fibrous substances extending in a direction approximately parallel to the longitudinal direction of the copper alloy wire. In the copper alloy wire of the present invention, when a cross section parallel to the longitudinal direction is observed, the average width (W) of the fibrous coherent precipitates coherently precipitated with the Cu of the parent phase and extending in the longitudinal direction of the copper alloy wire in a rectangular observation area of ​​240 nm x 360 nm is not particularly limited, but in order to further improve the effect of the coherent precipitates in preventing the deformation of the copper alloy wire, it is preferable that the average width (W) of the fibrous coherent precipitates coherently precipitated with the Cu of the parent phase and extending in the longitudinal direction of the copper alloy wire in a rectangular observation area of ​​240 nm x 360 nm is set to be equal to or larger than the following formula (II). (8.3×d)nm≦W≦(24.9×d)nm (II) (In formula (II), d represents the wire diameter (mm) of the copper alloy wire.) It is preferable that W is within the range of (9.0×d) nm≦W≦(24.0×d) nm. Therefore, in a preferred embodiment of the copper alloy wire of the present invention, the preferred range of the average width (W) of the coherent precipitates changes with the change in wire diameter. The above formula (II) is specified based on the wire diameter and the average width of the coherent precipitates in the examples of the present application described later.

[0033] If the average width (W) of the coherent precipitates is less than (8.3 × d) nm, the coherent precipitates will be thin relative to the wire diameter, and the effect of the coherent precipitates in preventing the deformation of the copper alloy wire may be limited. On the other hand, if it exceeds (24.9 × d) nm, the average width (W) will be large relative to the wire diameter, and the coherent precipitates will be thing However, the effect of preventing the deformation of the copper alloy wire may be limited.

[0034] [Average width (W) of precipitates that are coherent with the Cu in the matrix] In the copper alloy wire of the present invention, when a cross section parallel to the longitudinal direction is observed, the average length (L) of the fibrous coherent precipitates coherently precipitated in the parent phase Cu in a rectangular observation area of ​​240 nm × 360 nm extending in the longitudinal direction of the copper alloy wire is not particularly limited. However, in order to further improve the effect of the coherent precipitates in preventing the deformation of the copper alloy wire, it is preferable that the average length (L) of the fibrous coherent precipitates is greater than or equal to the following formula (III): (11.3 / d)nm≦L≦(33.8 / d)nm (III) (In formula (III), d represents the wire diameter (mm) of the copper alloy wire.) It is preferable that L is within the range of (14.0 / d) nm≦L≦(30.0 / d) nm. Therefore, in a preferred embodiment of the copper alloy wire of the present invention, the preferred range of the average length (L) of the coherent precipitates changes with the change in wire diameter. The above formula (III) is specified based on the wire diameter and the average length of the coherent precipitates in the examples of the present application described later.

[0035] If the average length (L) of the coherent precipitates is less than (11.3 / d) nm, the precipitates will be short relative to the wire diameter, and the effect of the coherent precipitates in preventing the deformation of the copper alloy wire may be limited. On the other hand, if it exceeds (33.8 / d) nm, the average length (L) will be large relative to the wire diameter, and the coherent precipitates will be thing However, the effect of preventing the deformation of the copper alloy wire may be limited.

[0036] [Average spacing (S) of precipitates that are coherent with Cu in the matrix] In the copper alloy wire of the present invention, when a cross section parallel to the longitudinal direction is observed, the average interval (S) of the coherent precipitates coherently precipitated in the Cu matrix in a rectangular observation area of ​​240 nm × 360 nm is, but is not particularly limited to, the following formula (IV): (760×x^-2.25)×dnm≦S≦(2300×x^-2.25)×dnm (IV) (In formula (IV), d is the wire diameter (mm) of the copper alloy wire, and x is the mass% of Ag.) Therefore, in a preferred embodiment of the copper alloy wire of the present invention, the preferred average of the coherent precipitates is changed according to the change in the wire diameter and the Ag content. Spacing(S) The above formula (IV) was derived from the experimental results in which the Ag content in the copper alloy wire was varied.

[0037] When the average interval (S) of the coherent precipitates is less than (760×x^-2.25)×dnm, the interval of the coherent precipitates becomes narrower relative to the wire diameter and Ag content, and the effect of the coherent precipitates in preventing the deformation of the copper alloy wire may be limited. On the other hand, when the average interval (S) of the coherent precipitates is more than (2300×x^-2.25)×dnm, the interval of the coherent precipitates becomes wider relative to the wire diameter and Ag content, and the effect of the coherent precipitates in preventing the deformation of the copper alloy wire may be limited.

[0038] [Coherent precipitates are aligned in the same crystal axis direction] In addition, in the copper alloy wire of the present invention, it is preferable that the coherent precipitates are aligned in the same crystal axis direction with respect to the Cu parent phase. "Aligned in the same crystal axis direction" means that the crystals of the Cu parent phase and the crystals of the coherent precipitates mainly composed of Ag are aligned in the same crystal axis direction. By having such a crystal arrangement, strain is generated between the crystals of the Cu parent phase and the crystals of the coherent precipitates. This strain hinders the copper alloy wire from deforming, so that the copper alloy wire is given a higher tensile strength.

[0039] Whether or not the coherent precipitates are coherent in the same crystal axis direction with respect to the Cu parent phase can be determined by the following method. First, a copper alloy wire sample is thinned by the focused ion beam (FIB) method, and a specified observation area (e.g., a rectangular observation area of ​​240 nm × 360 nm) is observed using a transmission electron microscope (TEM). The sample is cut parallel to the longitudinal direction, and the longitudinal direction is arranged horizontally during TEM observation.

[0040] Next, to confirm that the precipitates are coherently precipitated, a diffraction pattern is obtained as described above. At this time, the diffraction pattern can be taken at any zone axis incidence, for example, the image is taken at the

[0110] zone axis incidence, which generally makes the pattern easy to understand. The diffraction pattern due to the parent phase Cu crystals is observed to have the highest brightness, but other diffraction patterns are also observed, and by confirming a diffraction pattern with the same diffraction pattern type as Cu and a slightly narrow spot interval, it is confirmed that the precipitates are coherently precipitated.

[0041] Next, the angle of the sample is changed to obtain a diffraction pattern with the

[0100] or

[0111] zone axis incidence on the Cu parent phase, and it is confirmed whether or not a diffraction pattern with the same diffraction pattern type as Cu and a slightly narrower spot interval exists. If it is confirmed that the diffraction pattern is the same as Cu in both of the above two zone axis incidence axes, it is evaluated that the coherent precipitates are coherent in the same crystal axis direction with respect to the Cu parent phase.

[0042] [Method of manufacturing copper alloy wire of the present invention] Next, a method for producing the copper alloy wire of the present invention will be described. The method for producing the copper alloy wire of the present invention includes the steps of (a) melting a raw material, (b) casting the melted raw material to obtain an ingot, (c) subjecting the copper alloy material obtained from the ingot to a first heat treatment, (d) subjecting the copper alloy material obtained from the ingot to a second heat treatment after the first heat treatment, and (e) drawing the copper alloy material that has been subjected to the second heat treatment to a final wire drawing process with a working degree loge(A0 / A1 )( In the formula, A0 is a cross-sectional area in a direction perpendicular to the longitudinal direction of the copper alloy material immediately before the final wiredrawing, and A1 is a cross-sectional area in a direction perpendicular to the longitudinal direction of the copper alloy material immediately after the final wiredrawing) of 2.5 or more to obtain a copper alloy wire.

[0043] (a) the step of melting the raw materials and (b) the step of casting the melted raw materials to obtain an ingot can be carried out by a known general method. The raw materials used in the step (a) are blended in a predetermined ratio of each component so that Ag is 1.5 to 6.0 mass%, Mg is 0 to 1.0 mass%, Cr is 0 to 1.0 mass%, Zr is 0 to 1.0 mass%, and the balance is Cu.

[0044] (c) The heat treatment temperature in the step of subjecting the copper alloy material to the first heat treatment is 700°C or higher. If the temperature in the first heat treatment step is less than 700°C, it becomes difficult to form the precipitates mainly composed of Ag into a fibrous form during the final wire drawing process, and excellent tensile strength and vibration durability may not be obtained. The lower limit of the temperature in the first heat treatment step is preferably 750°C, and particularly preferably 800°C, in order to obtain a better tensile strength. On the other hand, the upper limit of the temperature in the first heat treatment step is not particularly limited, but is preferably 900°C.

[0045] The heat treatment time in the first heat treatment step is not particularly limited, but is preferably 0.1 to 10 hours, particularly preferably 0.5 to 5 hours, from the viewpoint of dispersing a large amount of precipitates and forming fibers in the subsequent steps.

[0046] After the first heat treatment step, the copper alloy material is cooled, and (d) a second heat treatment is further performed. The heat treatment temperature in the second heat treatment step is 350 to 600°C. If the heat treatment temperature in the second heat treatment step is less than 350°C or more than 600°C, precipitates mainly composed of Ag are not sufficiently precipitated, and excellent tensile strength and vibration durability may not be obtained. The heat treatment time in the second heat treatment step is not particularly limited, but is preferably 0.5 to 20 hours, and particularly preferably 1.0 to 15 hours.

[0047] After the second heat treatment process, the copper alloy material is cooled and (e) the final wire drawing process is performed. In the final wire drawing process, the degree of drawing loge(A0 / A1 )( In the formula, A0 is the cross-sectional area in the direction perpendicular to the longitudinal direction of the copper alloy material immediately before the final wiredrawing, and A1 is the cross-sectional area in the direction perpendicular to the longitudinal direction of the copper alloy material immediately after the final wiredrawing) is 2.5 or more. If the above-mentioned processing degree of the final wiredrawing is less than 2.5, the coherent precipitates cannot be sufficiently elongated and fiberized, and excellent tensile strength and vibration durability may not be obtained.

[0048] The degree of processing in the final wiredrawing process may be 2.5 or more in order to sufficiently elongate and fiberize the coherent precipitates, and the higher the degree of processing, the better the tensile strength. Therefore, the upper limit of the degree of processing in the final wiredrawing process is not particularly limited.

[0049] If necessary, intermediate wiredrawing may be performed between (b) the step of obtaining an ingot and (c) the first heat treatment step, and / or between (c) the first heat treatment step and (d) the second heat treatment step. The degree of processing in the intermediate wiredrawing is not particularly limited, but in order to increase the degree of processing in the final wiredrawing, it is preferable that the degree of processing be loge(B0 / B1 )( In the formula, B0 is the cross-sectional area in the direction perpendicular to the longitudinal direction of the copper alloy material immediately before the intermediate wiredrawing, and B1 is the cross-sectional area in the direction perpendicular to the longitudinal direction of the copper alloy material immediately after the intermediate wiredrawing) is preferably low, but in order to sufficiently precipitate the coherent precipitates and to sufficiently elongate and fiberize the coherent precipitates in the final wiredrawing, the above-mentioned working degree of the intermediate wiredrawing is preferably high. From the above, in terms of the balance between the two, the above-mentioned working degree is preferably 0 to 1.0.

[0050] In particular, by subjecting the copper alloy wire of the present invention to the above-mentioned (c) first heat treatment step and (d) second heat treatment step, it is possible to produce a copper alloy wire having excellent tensile strength even when the wire is made thin without impairing its excellent electrical conductivity. EXAMPLES

[0051] Next, examples of the present invention will be described, but the present invention is not limited to these examples as long as they do not depart from the spirit of the present invention.

[0052] Examples 1 to 40 Raw materials (oxygen-free copper, silver, magnesium, chromium and zirconium) were put into a graphite crucible so as to obtain the alloy composition shown in Table 1 below, and the temperature inside the crucible was heated to 1250°C or higher to melt the raw materials. A resistance heating furnace was used for melting. The atmosphere inside the crucible was a nitrogen atmosphere so that oxygen would not be mixed into the molten copper. After holding the temperature at 1250°C or higher for 3 hours or more, the cooling rate was set to 500 to 1000°C / s, and an ingot with a diameter (φ) of about 10 mm was cast in a graphite mold. After the start of casting, continuous casting was performed by appropriately putting in the above raw materials. In addition, when the raw materials contained chromium (Examples 23, 27, 28, 31, 33 and 34), the temperature inside the crucible was held at 1600°C or higher to melt the raw materials.

[0053] Next, the ingot obtained as described above was subjected to a first heat treatment at the temperature and time shown in Table 1 below. After the first heat treatment step, the test material was subjected to intermediate wire drawing to a diameter of φ8 mm, and further, a second heat treatment was performed at the temperature and time shown in Table 1 below. After the second heat treatment step, a final wire drawing was performed at a predetermined drawing rate to a wire diameter shown in Table 1 below, to obtain a copper alloy wire. The first heat treatment and the second heat treatment were performed in a batch furnace in a nitrogen atmosphere.

[0054] Comparative Examples 1 to 7 In Comparative Examples 1, 4 to 7, a copper alloy wire was obtained by the same process as in the above-mentioned Examples and under the manufacturing conditions shown in Table 1 below, except that an ingot having a size of about φ8 mm was cast and drawn to φ0.1 mm in a final drawing process without intermediate drawing. In Comparative Example 2, a copper alloy wire was obtained by the same process as in Comparative Examples 1, 4 to 7, except that the first heat treatment and the second heat treatment were not performed. In Comparative Example 3, a copper alloy wire was obtained by the same process as in Comparative Examples 1, 4 to 7, except that the second heat treatment was not performed. Therefore, in Comparative Example 3, the first heat treatment was performed at φ8 mm.

[0055] [Method of observing precipitates that are coherently precipitated with Cu in the parent phase] The copper alloy wires in the examples and comparative examples were thinned by the FIB method, and a rectangular observation area with a cross-sectional (short-side) length of 240 nm and a longitudinal length of 360 nm was observed using a transmission electron microscope (TEM). The copper alloy wires were cut parallel to the longitudinal direction, and the longitudinal direction was arranged horizontally during TEM observation. Next, a diffraction pattern was obtained to confirm that the precipitates were precipitated in a consistent manner. At this time, the diffraction pattern was imaged with a

[0110] zone axis incidence, which is generally easy to understand. The diffraction pattern due to the crystals of the parent phase, Cu, was observed with the highest brightness, but other diffraction patterns were also observed, and the precipitates in the diffraction pattern were identified as Ag by measuring the type of the diffraction pattern and the spot interval.

[0056] Next, when the objective aperture is inserted so that only the diffraction waves of the diffraction pattern of the precipitates obtained above can be selected and observed, only the parts generating the diffraction waves that form the diffraction pattern (i.e., the coherent precipitates) are observed brightly. This is called a dark-field image, and this dark-field image (shown in FIG. 2) was taken for the copper alloy wires in the examples and comparative examples. From the dark-field images obtained above, the area ratio, average width, average length, and average spacing of the precipitates (coherent precipitates) that are coherently precipitated in the Cu matrix were calculated as follows.

[0057] First, the contrast obtained from the dark-field image was binarized. The p-tile method was used for binarization. When the p-tile method is used, the threshold is determined without changing the order of brightness, so photographs taken of the same area in different observation environments can be binarized in a similar manner. However, this is premised on the fact that the environment is not one in which brightness changes in local areas on the image. After that, the number of pixels of the white contrast area, i.e., the precipitates that are coherently precipitated (coherent precipitates), was calculated out of the total number of pixels in the obtained photograph, and the number of pixels of the coherent precipitates was divided by the total number of pixels to calculate the area ratio.

[0058] In addition, the number of pixels of the coherent precipitates in the longitudinal direction was calculated using the cross-sectional direction of the dark field image as the row number, and the number of pixels for each row was graphed as shown in Figure 3. The row numbers 0 to 275 observed in Figure 3 correspond to a length of 240 nm in the cross-sectional direction. The part with a pixel number of 25 or more was considered as one peak, and the half-width of each peak was defined as the width of the coherent precipitate. The width of the coherent precipitate was calculated from each peak, and the average value was calculated to obtain the average width. The maximum value of the above peak was defined as the length of the coherent precipitate, and the length of the coherent precipitate was calculated from the number of pixels of each peak relative to the total number of pixels in the photograph, and the average value was calculated to obtain the average length. The distance between the maximum value of the above peak and the maximum value of the adjacent peak was measured, and each distance was defined as the distance of the coherent precipitate. The distance between each peak was calculated, and the average value was calculated to obtain the average distance of the precipitate.

[0059] In addition, the above-mentioned aspects of the coherent precipitates were calculated with the sample thickness of the thin film set to 0.15 μm as the reference thickness. When the thickness of the copper alloy wire is different from the reference thickness, the thickness of the copper alloy wire is converted to the reference thickness, that is, the dispersion density calculated based on the photograph is multiplied by (reference thickness / copper alloy wire thickness) to calculate the dispersion density. In the examples and comparative examples, the sample thickness was set to about 0.15 μm in all copper alloy wires by the FIB method.

[0060] [Method for evaluating whether coherent precipitates are aligned in the same crystal axis direction with respect to the Cu parent phase] As described above, in order to confirm that the precipitates are precipitated coherently, a diffraction pattern is obtained with the

[0110] zone axis incidence on the Cu parent phase, and in order to confirm that the coherent precipitates are aligned in the same crystal axis direction in the Cu parent phase, a diffraction pattern is obtained with the

[0110] or

[0111] zone axis incidence on the Cu parent phase while changing the angle of the sample. This procedure was followed to evaluate whether the coherent precipitates are aligned in the same crystal axis direction in the Cu parent phase. In Table 1, if the coherent precipitates are aligned in the same crystal axis direction in the Cu parent phase, they are indicated with an O, and if they are not aligned, they are indicated with an X.

[0061] [Method of measuring tensile strength] A tensile test was performed using a precision universal testing machine (manufactured by Shimadzu Corporation) in accordance with JIS Z2241 to determine the tensile strength (MPa). The above test was performed on three copper alloy wires, and the average value (N=3) was calculated to determine the tensile strength of each copper alloy wire.

[0062] [Conductivity measurement method] The electrical conductivity was measured by measuring the resistivity of three test pieces, each 300 mm long, in a thermostatic bath maintained at 20°C (±0.5°C) using the four-terminal method, and calculating the average electrical conductivity. The distance between the terminals was 200 mm.

[0063] [Table 1]

[0064] As shown in Table 1 above, in Examples 1 to 40 in which the first heat treatment step at 700°C or higher and the second heat treatment step at 350 to 600°C were performed and the area ratio of the coherent precipitates was (0.393×x-0.589)%≦A≦(3.88×x-5.81)% (wherein x represents the mass % of Ag), a copper alloy wire having excellent tensile strength could be obtained without impairing excellent electrical conductivity, even when the wire was thinned to 0.02 mm to 2.6 mm.

[0065] On the other hand, in Comparative Example 1 in which 8.0 mass% Ag was added, the electrical conductivity was significantly decreased. In Comparative Example 2 in which the first and second heat treatment steps were not performed, no coherent precipitates were obtained, and good tensile strength was not obtained, compared with Example 4, which had the same manufacturing conditions and composition as Comparative Example 2 except for the first and second heat treatment steps. In Comparative Example 3 in which the second heat treatment step was not performed, Comparative Examples 4 and 6 in which the temperature of the second heat treatment step was as low as 300°C, and Comparative Examples 5 and 7 in which the temperature of the second heat treatment step was as high as 700°C, no coherent precipitates were obtained, and good tensile strength was not obtained.

Claims

1. A copper alloy wire having an alloy composition containing 1.5 to 6.0 mass% Ag, 0 to 1.0 mass% Mg, 0 to 1.0 mass% Cr, and 0 to 1.0 mass% Zr, with the balance being Cu and unavoidable impurities, When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the area ratio (A) of precipitates that are precipitated in a coordinated manner with Cu of the parent phase in a rectangular observation area of ​​240 nm × 360 nm is The following formula (I) (0.393×x-0.589)%≦A≦(3.88×x-5.81)% (I) (In formula (I), x represents the mass % of Ag.) is within the range A copper alloy wire in which the precipitates, which are precipitated in conformity with the Cu of the parent phase, are present in a fibrous form along the longitudinal direction of the copper alloy wire.

2. 2. The copper alloy wire according to claim 1, wherein the total content of at least one component selected from the group consisting of Mg, Cr and Zr is 0.01 to 3.0 mass%.

3. When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the average width (W) of the precipitates precipitated in alignment with the Cu of the parent phase in a rectangular observation area of ​​240 nm × 360 nm is The following formula (II) (8.3×d)nm≦W≦(24.9×d)nm (II) (In formula (II), d represents the wire diameter (mm) of the copper alloy wire.) 3. The copper alloy wire according to claim 1, wherein the copper alloy wire is in the range of

4. When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the average length (L) of the precipitates precipitated in a rectangular observation area of ​​240 nm × 360 nm in accordance with the Cu of the parent phase is The following formula (III): (11.3 / d)nm≦L≦(33.8 / d)nm (III) (In formula (III), d represents the wire diameter (mm) of the copper alloy wire.) The copper alloy wire according to any one of claims 1 to 3, wherein the copper alloy wire is in the range of

5. When a cross section parallel to the longitudinal direction of the copper alloy wire is observed, the average interval (S) of the precipitates precipitated in a rectangular observation area of ​​240 nm × 360 nm is The following formula (IV): (760×x^-2.25)×dnm≦S≦(2300×x^-2.25)×dnm (IV) (In formula (IV), d represents the wire diameter (mm) of the copper alloy wire, and x represents the mass% of Ag.) The copper alloy wire according to any one of claims 1 to 4, wherein the copper alloy wire is in the range of

6. The copper alloy wire according to claim 1 , wherein the precipitates are aligned in the same crystal axis direction with respect to the Cu of the parent phase.

7. 7. A method for producing a copper alloy wire according to claim 1, comprising the steps of: melting a raw material; casting the melted raw material to obtain an ingot; subjecting the copper alloy material obtained from the ingot to a first heat treatment; and further subjecting the copper alloy material to a second heat treatment; and subjecting the copper alloy material subjected to the second heat treatment to a final wire drawing process to obtain a copper alloy wire, The first heat treatment step is carried out at a temperature of 700° C. or higher, The second heat treatment step is carried out at a temperature of 350 to 600° C., The degree of processing loge (A0 / A1) (wherein A0 is a cross-sectional area in a direction perpendicular to the longitudinal direction of the copper alloy material immediately before the final wiredrawing, and A1 is a cross-sectional area in a direction perpendicular to the longitudinal direction of the copper alloy material immediately after the final wiredrawing) of the final wiredrawing process is 2.5 or more, An intermediate wire drawing process is performed between the first heat treatment step and the second heat treatment step, The manufacturing method of the copper alloy wire, wherein the degree of processing loge (B0 / B1) of the intermediate wiredrawing (wherein B0 is a cross-sectional area in a direction perpendicular to the longitudinal direction of the copper alloy material immediately before the intermediate wiredrawing, and B1 is a cross-sectional area in a direction perpendicular to the longitudinal direction of the copper alloy material immediately after the intermediate wiredrawing) is more than 0 and is not more than 1.0.

Citation Information

Patent Citations

  • Radio wave absorbing device

    JP1993090832A

  • Cu-Ag ALLOY WIRE AND METHOD FOR PRODUCING Cu-Ag ALLOY WIRE

    JP2011246802A

  • High flexural fatigue resistant copper-based alloy wire

    JP2017002337A

  • Cu-Ag ALLOY WIRE HAVING HIGH STRENGTH AND HIGH CONDUCTIVITY AND METHOD FOR MANUFACTURE THEREOF

    WO2007046378A1